2003
DOI: 10.1051/forest:2003061
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vegetation management and the wood and pulping properties of a Eucalyptus hybrid clone

Abstract: -When felled at 7 years of age, Eucalyptus grandis × camaldulensis trees from three vegetation management treatments (manually weeded treatment, 1.2 m row weeding treatment and a weedy control) were tested for selected wood and pulping properties in a trial in Zululand, South Africa. Weed control significantly improved merchantable volume of the manually weeded (230 m 3 ha −1 ) treatment over that of the 1.2 m row weeding (171 m 3 ha −1 ) or weedy control (138 m 3 ha −1 ). A significant increase in fibre lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…These findings are coincident with those of Snook et al (1986). Thus, the increase in growth generated by weed control and fertilization does not necessarily result in a decrease in wood quality as reported by other authors (Little et al 2003;Efhami et al 2012). These findings are coincident with those of Snook et al (1986).…”
Section: Growth Parameters and Wood Propertiessupporting
confidence: 61%
See 2 more Smart Citations
“…These findings are coincident with those of Snook et al (1986). Thus, the increase in growth generated by weed control and fertilization does not necessarily result in a decrease in wood quality as reported by other authors (Little et al 2003;Efhami et al 2012). These findings are coincident with those of Snook et al (1986).…”
Section: Growth Parameters and Wood Propertiessupporting
confidence: 61%
“…Nevertheless, most references indicated that with diffuseporous species, there is no relationship between growth rate and wood density (DeBell et al 2002;Zhang et al 2003;Pliura et al 2005), which agrees with the results of this work. Most studies describing the effects of weed control and fertilization on wood quality only include short-term effects, for periods lasting from several months to 2 years (Wilkins and Horne 1991;Little et al 2003). In the very short term, important structural changes in wood cells that form under different fertilizer concentrations usually occur (Luo et al 2005;Pitre et al 2007).…”
Section: Growth Parameters and Wood Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Little et al (2003) stated for Eucalpytus that if wood density rises above 300 kg/m 3 , there is a decline in paper strength in terms of tensile, burst and folding endurance. In our study we found significant height effects only with tear index, zero span tensile strength and opacity suggesting that the within-tree variability for these properties is less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…An increased growth rate during the early stages of development will necessarily modify the amount of wood in areas close to the pith. These changes may also strongly alter the quality of this stem, particularly in species with short production cycles (10 years) (De Bell et al, 1998;Little et al, 2003;Efhami et al, 2012). Studies in Populus have reported different stages of xylem maturation in cellular components of the same age, although this varies 2 the short-term (years 1 and 3) and long-term (year 10) effects of the treatments on wood characteristics.…”
Section: Introductionmentioning
confidence: 99%